Mediasi Kepuasan Kerja Pada Hubungan Lingkungan Kerja Dengan Retensi Karyawan - Guntur Prastya; Eko Nur Fu'ad (Universitas Islam Nahdlatul Ulama Jepara, 2022)
This study aims to analyze the effect of organizational culture, work environment, and job satisfaction on employee retention. With saturated sampling technique, the entire population of 121 employees at PT. SSF was used as the research sample. The data collection used a survey method with a questionnaire instrument. Hypothesis testing was carried out using the Structural Equation Modeling approach with the Partial Least Square tool. The results showed that organizational culture has no effect on job satisfaction. However, this study found that work environment partially affects job satisfaction, organizational culture partially affects employee retention, work environment partially affects employee retention, and job satisfaction partially affects employee retention. This study also examines the indirect effect on employee retention which proves that job satisfaction mediates the relationship between work environment and employee retention. The implication of the results of this study is that a comfortable work environment is an element that must be met as a company's effort to retain employees. However, the company's retention efforts will be more successful if the work environment can increase job satisfaction to make employees feel more comfortable working in the company.